Elbow arthroscopy: state of the art. Issue 5 (10th October 2017) - Pederzini, Luigi A; Di Palma, Felice; Safran, Marc R; Bain, Gregory I
Abstract : Due to the minimally invasive nature of arthroscopic surgery, patients recover more quickly and are able to initiate rehabilitation and functional activities sooner than with open approaches. Elbow arthroscopy had initially been considered a tool for loose body removal and diagnostic purposes only. However, as a better understanding of elbow anatomy and pathology has evolved, coincident with better instrumentation, elbow arthroscopy is now being used for an increasing list of indications. Current indications for elbow arthroscopy have expanded to include loose bodies removal, and the treatment of degenerative arthritis, septic arthritis, inflammatory arthritis, lateral epicondylitis, osteochondritis dissecans, synovitis, radial head deformity, post-traumatic arthrofibrosis, posterolateral rotatory instability, posteromedial impingement and plica, in addition to the management of some elbow fractures, including fractures of the capitellum, coronoid and radial head. Elbow arthroscopy does have limitations and particular surgical risks; however, these can be minimised. Elbow arthroscopy can be performed safely with appropriate knowledge of the articular and periarticular anatomy, in addition to precise surgical technique and understanding the limitations of elbow arthroscopy as well as the limitations of the experience of the surgeon.